1999
DOI: 10.1055/s-2007-971105
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory, Lactate-Derived and Catecholamine Thresholds During Incremental Treadmill Running: Relationship and Reproducibility

Abstract: Anaerobic threshold as a basic criterion of training recommendation can be estimated by various parameters. The purpose of this study was to investigate the relationship and the reproducibility of ventilatory, lactate-derived and catecholamine thresholds of an incremental treadmill exercise. Therefore, 11 male subjects underwent two incremental treadmill tests within 7 days. The lactate threshold (LT) was determined at the lowest value of the lactate-equivalent (ratio lactate/performance). The individual anaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
140
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 6 publications
5
140
0
8
Order By: Relevance
“…Based on the running velocity at the lactate threshold as well as at the level of v-4mM lactate, Mc Millan et al [11] also demonstrated a significant increase of endurance capacity (1.29 km/h (LT); 1.05 km/h (v-4mM)) of british youth soccer players. His subjects were initially tested at the beginning of the preseason phase after the summer intermission and retested at six time points throughout a soccer season.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the running velocity at the lactate threshold as well as at the level of v-4mM lactate, Mc Millan et al [11] also demonstrated a significant increase of endurance capacity (1.29 km/h (LT); 1.05 km/h (v-4mM)) of british youth soccer players. His subjects were initially tested at the beginning of the preseason phase after the summer intermission and retested at six time points throughout a soccer season.…”
Section: Discussionmentioning
confidence: 98%
“…As generally known, submaximal blood lactate assessment is a useful tool for detecting changes in endurance fitness of soccer players [6,11,12]. Some authors even describe determining lactate threshold to possibly be a more sensitive indicator of aerobic endurance performance than determining maximum oxygen uptake (VO 2 max ) [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Entre esses fatores, está a economia de corrida (EC) que pode ser definida como o estado estável do VO 2 para uma dada velocidade submáxima ou distância [12][13][14][15] , e na habilidade do sistema neuromuscular em produzir potência durante o exercício 23 (r=0,97), no limiar ventilatório (r=0,88) e no ponto de compensação respirató-ria (r=0.95). Em ambos os testes foi encontrada uma forte correlação (r = 0,97; p < 0,01) entre o limiar anaeróbio individual e o ponto de compensação respiratória 9,12 .…”
Section: Discussionunclassified
“…Em ambos os testes foi encontrada uma forte correlação (r = 0,97; p < 0,01) entre o limiar anaeróbio individual e o ponto de compensação respiratória 9,12 . Diante disso, embora fosse importante mensurar a concentração sanguínea de lactato e bicarbonato durante as fases de transição no TCPE, os estudos citados permitem assumir que a interpretação dos limiares por parâmetros ventilatórios apresenta similitude com os limiares detectados invasivamente.…”
Section: Discussionunclassified
See 1 more Smart Citation